2018
DOI: 10.48550/arxiv.1804.10013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distributed Ledger Technology: Blockchain Compared to Directed Acyclic Graph

Abstract: Nowadays, blockchain is becoming a synonym for distributed ledger technology. However, blockchain is only one of the specializations in the field and is currently well-covered in existing literature, but mostly from a cryptographic point of view. Besides blockchain technology, a new paradigm is gaining momentum: directed acyclic graphs. The contribution presented in this paper is twofold. Firstly, the paper analyzes distributed ledger technology with an emphasis on the features relevant to distributed systems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Benčić and Žarko [101,102] conducted a comparative study focused at evaluating two types of DLTs i.e. blockchains and DAGs.…”
Section: Approaches Analyzing Blockchain Scalabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Benčić and Žarko [101,102] conducted a comparative study focused at evaluating two types of DLTs i.e. blockchains and DAGs.…”
Section: Approaches Analyzing Blockchain Scalabilitymentioning
confidence: 99%
“…The section presented (See table 11) some of the empirical / theoretical studies analyzing the scalability of blockchain that we found during our survey. various comparative studies including [101], [102], [105], [103], encompassing different blockchain technology aspects are analyzed,…”
Section: Summary Of Approaches Analyzing Blockchain Scalabilitymentioning
confidence: 99%
“…Scalability measurements were made: version 2 showed an average speed of 2,234 tps and version 3 -3,600 tps. The distributed protocol relies on the Directed Acyclic Graph (DAG) [15], [16] with rapid finality Proof-of-Stake (PoS) consensus. The launch of the public mainnet is scheduled for this autumn.…”
Section: Platform Overviewmentioning
confidence: 99%
“…Such a model produces a constant and continue increasing of its size and this generates a crucial scalability issue that must be effectively faced in the future [20]. By way of example, at the beginning of 2018 the size of Bitcoin ledger has been evaluated about 145-gigabyte and that of Ethereum ledger about 40-gigabyte [11].…”
Section: Consensus Mechanismmentioning
confidence: 99%
“…return R 9: end procedure 11 A management tool able to display, track and analyze a series of information.…”
mentioning
confidence: 99%